The Effect of Acetonitrile Solvent on the Quantitative Determination of Europium (III) by Voltammetry and its Optimization using the Box-Behnken Design - Uji Pratomo; Ari Hardianto; Yeni Wahyuni Hartati; Husein Hernandi Bahti; Santhy Wyantuti (Syarif Hidayatullah State Islamic University, 2022)
There is often a drawback during the determination of Eu in aqueous solvents using the voltammetric method. The current signal from water can reduce that of the element, which causes difficulty while separating the Eu signal from other rare earth elements (REE). Therefore, this study used acetonitrile as a solvent due to its high electrical conductivity and wide potential range. The optimum conditions for the determination of Eu in acetonitrile using the Box-Behnken design include 74.56 seconds deposition time, 0.125 V amplitude modulation, and -2.0 V potential deposition. The platinum electrode's performance showed a recovery value of 98.91% and accuracy and precision (in %RSD) of 96.67% and 1.11%, respectively. Furthermore, detection and quantitation limits of 0.6 mg/L and 5.1 mg/L were recorded from the analysis. It concluded that the differential pulse voltammetry method was applied to determine the presence of Eu in acetonitrile.